An Overview of Pekan Lightning Detection System (PLDS) - Wan Ismail, Ibrahim; Mohd Riduwan, Ghazali (IEEE, 2012)
Pekan is located at east of peninsular Malaysia which experience very high cloud to ground (CG) lightning density. The lightning strike hazards can be properly managed by using a lightning location system (LLS). In this paper, a system to monitor the lightning strikes and thunderstorm has been installed and setup. Pekan Lightning Detection System (PLDS) has a combination of Magnetics Direction Finder and Time-of–Arrival sensor. The PLDS provides both real-time and historical lightning data .The real-time data include the time of lightning strokes, their location and an estimate of the peak current.